Is the 'hybrid turn' a 'spatial turn'? A geographical perspective on hybridity and state-formation in the Western Pacific. Issue 4 (4th July 2017) - Allen, Matthew G.; Dinnen, Sinclair
Abstract: Our point of departure is the emerging critique of the problematic treatment of scale across various disciplinary engagements with hybridity. Adopting an overarching state-formation perspective, we extend this geographical critique by combining the sociospatial lenses of scale and territory in an analysis of one of the primary animators of political economic change and contestation in post-colonial Melanesia: extractive resource capitalism. Focusing on the Solomons Group of islands, we examine two spatial phenomena at the core of the contentious and frequently violent politics of extraction animating processes of state-formation in these settings: the social and historical production of islands as a scale/territory of violent struggle; and the emergence of the 'ideology of customary landownership' as a territorialising and exclusionary project that also has salient scalar dimensions. While these phenomena illustrate the inadequacy of hybridity's crude spatial ontology, they also demonstrate how hybridity perspectives can play a role in achieving 'thick description' of the complex interactions involved in spatialised political economic processes. We conclude by sketching out some agendas for research on the political economy of resource extraction – and, more broadly, state-formation – in the western Pacific that combine spatial perspectives with those of the critical hybridity literature across various social science fields.